Assessing the direct economic value of cruise tourism in a port of call: The case of Funchal on the island of Madeira. (October 2019) - Gouveia, André XS; Eusébio, Celeste
In recent years, the economic relevance of cruise tourism has increased considerably. However, there are still many doubts regarding the real economic value of this industry in a port of call. This paper presents a methodology to estimate the total expenditures carried out in a port of call. The port of Funchal on the island of Madeira was used as a case study, given the great relevance of the cruise tourism industry to this port of call. A combination of several methods, and of secondary and primary data, was used to assess the total expenses of the cruise passengers, crew members, and cruise lines. Results reveal that, although cruise tourism has an important role in the economic development of the island of Madeira nowadays, several strategies should be adopted to increase this relevance. Therefore, the paper ends with some implications for increasing the direct economic value generated by cruise tourism.